2016
DOI: 10.1515/opli-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Reporting from the Field: The Narrative Reconstruction of Experience in Pick-up Artist Online Communities

Abstract: This study focuses on the reconstruction of experience in the online environment of the Pick-up Artist (PUA) community forums and aims to uncover yet another facet of personal narrative, namely the role and performance of framing in the reporting of events. Discursive psychologists have often pointed out that a narrative is not a precise reflection of reality but a device that itself shapes the social world because reality always under-determines the verbal representation of events. In this study, we show how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Lastly, pick-up artists use formulaic tactics known as ‘game’ to convince women to sleep with them. Dayter and Rüdiger (2016: 338) gathered a corpus of 27 posts, comprising 37,000 words of running text, from the Field Reports section of a pick-up artist forum. They observed that the users were concerned with achieving physical intimacy as opposed to developing a mutual connection, and that the community use terms drawn from sales and marketing for kissing (‘kiss-closed’), getting a woman’s phone number (‘number-closed’) and chatting (‘used the common travellers’ lines’).…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, pick-up artists use formulaic tactics known as ‘game’ to convince women to sleep with them. Dayter and Rüdiger (2016: 338) gathered a corpus of 27 posts, comprising 37,000 words of running text, from the Field Reports section of a pick-up artist forum. They observed that the users were concerned with achieving physical intimacy as opposed to developing a mutual connection, and that the community use terms drawn from sales and marketing for kissing (‘kiss-closed’), getting a woman’s phone number (‘number-closed’) and chatting (‘used the common travellers’ lines’).…”
Section: Introductionmentioning
confidence: 99%
“…King'in çalışmasına göre ise, tavlama sanatçılığı kılavuzları olarak bilinen "tavsiye kılavuzlarının, kadınların erkeklerle ilişkilerinde ve bu ilişkilerin sürdürülmelerine yardımcı olacak bir araç olarak özgüven kavramının nasıl vurguladığını göstermektedir (2020)." Tavlama sanatçısı terimi Dayter ve Rüdiger'e göre, "internet üzerinde erkeklerin birbirleri için yeni flört tavsiyelerini konu alan, şok edici bir şekilde araçsal, adeta bir iş gibi yapılan ve hiç "romantik olmayan" bir retorik sistem üzerinde şekillenen bir konuşma sanatı olarak ortaya atılmıştır ve bu tavsiyeleri uygulayanlar birbirlerine "tavlama sanatçısı" (pick-up artist) adını vermektedir (Dayter & Rüdiger, 2016). Tavlama sanatçıları, Kırmızı Hapçı bir pozisyondan, tabak çevirme taktiğini kullanarak belirli manipülatif dil oyunlarını kullanmak sureti ile kadınlarla tanışan ve bu iletişimsel performans esnasında kadınlara içkin bazı açıkları keşfederek bu açıkları sosyal mecralarda yayan kişiler olarak da bilinebilirler.…”
Section: Sonuççu Argümanunclassified
“…With regard to PUAs more specifically, Cosma and Gurevich (2018: 95) find that PUAs endorse a narrowly defined hegemonic masculinity while rejecting alternative masculinities, and that PUA leaders position themselves as 'authoritative voices' on selfimprovement in pursuit of this idealised masculinity. Shifting the focus away from masculine identity construction and towards the discourse of 'pick-up', Dayter and Rüdiger (2016) analyse the reconstruction of experience through narrative in a corpus of 37 posts from PUA forums, focusing on PUAs 'field reports', which are 'narrative constructions of encounters between the PUAs and women' (Dayter and Rüdiger, 2016: 337). Their analysis demonstrated how the field reports are used by posters to index and verify their membership in the community, and are underpinned by a frame of 'success' in which almost any outcome or response from women in the encounter is constructed as being successful and as the PUA achieving their goal.…”
Section: The Pick-up Artist Communitymentioning
confidence: 99%